Production of Piptadenia moniliformis B. seedlings irrigated by waste water from shrimp farming - Silveira, Gleydson Vinicius dos Santos; Holanda, Alan Cauê de; Alves, Allyson Rocha; Costa, Jenickson Rayron da Silva [UNESP]; Pinheiro, Ewerton Souto (Centro Universitario de Maringa, 2022)
The effect of irrigation with different saline concentrations of water from shrimp farming on the early development of Piptadenia moniliformis Benth seedlings was analyzed. Assay was conducted in a shade house at the Universidade Federal Rural do Semi-árido (UFERSA) by a totally randomized design with one species, five treatments and seven replications. Treatments comprised irrigation with distilled (control) and saline water, with different electrical conductivities: 2.1; 3.05; 4.83; 6.84 mS cm-1. Plastic trays were used containing coconut fiber and planted with one seed per cell. They were replanted in polyethylene bags (820 cm3) twelve days after germination, with substrate featuring organic compound and sand at 2:1. Daily, by the end of the day, seedlings were irrigated with 100 ml of water per recipient. Evaluations of morphological parameters (height, diameter and number of leaves) were undertaken every fortnight; finally, the dry matter of root, stalk and leaves was evaluated. After 60 days from replanting, control and treatment with the lowest saline rate (2.1 mS cm-1) had the greatest increase in height (17.57 and 16.18 cm), diameter (2.96 and 2.71 mm), the greatest number of leaves (10.00 and 8.42) and highest rates IQD (0.1971 and 0.1320, respectively). Growth of Piptadenia moniliformis seedlings decreased as electrical conductivity increased. Within the study's conditions, species was tolerant to irrigation water at electrical conductivity 2.1 mS cm-1
Produção de mudas de Piptadenia moniliformis B. irrigadas com água residuária da carcinicultura
Keywords: Catanduva; Forest greenhouses; Reusage of water; Salt water stress; Vegetal production